2012
DOI: 10.5301/ejo.5000082
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Sensation of Conjunctival Autograft after Pterygium Surgery

Abstract: Anesthesia at first month and hypoesthesia at second and third month at conjunctival autograft was observed after pterygium surgery. Additionally, hypoesthesia was observed at nasal cornea and superior bulbar conjunctiva at the first month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…However, Sakarya et al 9 reported that 1 month after surgery nasal CS was significantly reduced compared to initial values. It is worth mentioning that, surgical procedures in both studies were similar except for the use of fibrin glue and a pressured eye patch during 1 week in Sakarya's work.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, Sakarya et al 9 reported that 1 month after surgery nasal CS was significantly reduced compared to initial values. It is worth mentioning that, surgical procedures in both studies were similar except for the use of fibrin glue and a pressured eye patch during 1 week in Sakarya's work.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, previous data 9 suggest that CS is not at all recovered and nothing is known about factors that could affect the process. To know these factors could help clinicians to establish the right time for surgery with a successful and speed CS recovery, thus protecting the ocular surface.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In one study, patients with pterygium had lower Schirmer's test results and tear film stability [12], and tear film break-up times (TBUTs) have been found to increase significantly after primary pterygium excision [13,14]. Furthermore, hypoesthesia has been reported in the nasal corneas of patients with pterygium [15,16]. In this regard, corneal sensitivity is a measure of corneal nerve function and indicates the integrity of the protective mechanisms of the ocular surface.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, complete recovery is usually achieved by 1 month after pterygium excision [25]. Even though sensitivity is decreased in pterygium-affected corneas [15,16], no previous investigations have studied how corneal sensitivity is related to lesions in the corneal nerve fibers in patients with pterygium. Moreover, several studies have reported that corneal sensitivity recovers before reinnervation after corneal surgery [26,27].…”
Section: Introductionmentioning
confidence: 99%